2017
DOI: 10.3329/pa.v28i3.34659
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pellet from total mixed ration on growth performance, blood metabolomics, carcass and meat characteristics of Bangladeshi garole sheep

Abstract: Six indigenous Bangladeshi Garole sheep (Ovis aries) (BW: 8±0.5 kg; Age: 1yr) were divided into two groups using a randomized block design to investigate the effect of total mixed ration (TMR) pellet feeding on growth parameter, blood metabolomics, carcass and meat characteristics. Control diet was composed of road side grass, rice straw, wheat bran, mustard oil cake, molasses, common salt which considered as loose total mixed ration (L-TMR) and treatment diet was pelleted form of L-TMR (P-TMR).In both the die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 7 publications
4
15
1
Order By: Relevance
“…Such gain may be attributed to the prevailed Ta on one hand and the diet type (pelleted diet) on the other hand. Numerous studies have substantially shown that the processing methods of reducing the physical form of forages used in pelleted diet have effects on the rate at which digesta leave the rumen, which in turn controls voluntary feed intake, digestibility, and utilization [36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…Such gain may be attributed to the prevailed Ta on one hand and the diet type (pelleted diet) on the other hand. Numerous studies have substantially shown that the processing methods of reducing the physical form of forages used in pelleted diet have effects on the rate at which digesta leave the rumen, which in turn controls voluntary feed intake, digestibility, and utilization [36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…This led to the recent trend to offer partially or completely pelleted TMR to dairy cows and heifers in some regions of the world ( 5 7 ). The use of pelleted TMR has also been reported for goat ( 8 , 9 ) and sheep production ( 10 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, increased DMI and DM digestibility for PTMR cows resulted in a higher ADG and a lower FCR, which was consistent with findings when a PTMR was fed to meat sheep (Islam et al . ). The cost associated with pelleting TMR was 20 US dollar per tonne feed, including manual work, water, electricity and machinery depreciation, but more costs associated with transportation, storage and labour were accordingly saved by using PTMR in this study.…”
Section: Discussionmentioning
confidence: 97%
“…However, altering the form of feeds did not change blood metabolomics between GTMR‐fed versus PTMR‐fed sheep (Islam et al . ). In this study, dietary treatments did not cause significant effects of PTMR on blood metabolites, but PUN and glucose concentrations increased over feeding period.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation